Building a National Program for Pilot Studies of Embedded Pragmatic Clinical Trials in Dementia Care. (26th June 2020) - Brody, Abraham A.; Barnes, Deborah E.; Chodosh, Joshua; Galvin, James E.; Hepburn, Kenneth W.; Troxel, Andrea B.; Hom, Kimberly; McCarthy, Ellen P.; Unroe, Kathleen T.
Abstract : Sixteen million caregivers currently provide care to more than 5 million persons living with dementia (PLWD) in the United States. Although this population is growing and highly complex, evidence‐based management remains poorly integrated within healthcare systems. Therefore, the National Institute on Aging IMPACT Collaboratory was formed to build the nation's ability to conduct embedded pragmatic clinical trials (ePCTs) for PLWD and their caregivers. The pilot core of the IMPACT Collaboratory seeks to provide funds for upward of 40 pilots for ePCTs to accelerate the testing of nonpharmacologic interventions with the goal that these pilots lead to full‐scale ePCTs and eventually the embedding of evidence‐based care into healthcare systems. The first two challenges for the pilot core in building the pilot study program were (1) to develop a transparent, ethical, and open nationwide process for soliciting, reviewing, and selecting pilot studies; and (2) to begin the process of describing the necessary components of a pilot study for an ePCT. During our initial funding cycle, we received 35 letters of intent, of which 17 were accepted for a full proposal and 14 were submitted. From this process we learned that investigators lack knowledge in ePCTs, many interventions lack readiness for an ePCT pilot study, and many proposed studies lack key pragmatic design elements. We therefore have set three key criteria that future pilot studies must meet at a minimum to be considered viable. We additionally discuss key design decisions investigators should consider in designing a pilot study for an ePCT. J Am Geriatr Soc 68:S14–S20, 2020 .